Goods and Services Tax (GST) Networking and its working process - KUMAR, P NARESH (IJRDO - Journal of Business Management, 2018)
A reform in every step will be an added advantage to every individual, society and also for State. A special case may be the Tax Environment of every country. A reform in the Government Tax System will be a definite help for the country to grow. To move ahead, Goods and Services Tax (GST) is an instrument in the indirect tax system of the country. Has it supports the execution of transparency and eliminates the tax burden between the Inter-states. This paper helps us to know about the Goods and Services Tax (GST) approach the networking and also an idea about its working process. It clears on the view that what are the unresolved problems in achievement of GST approach in our India and also discussing benefits of GST for common man and for the business sectors. GST mechanism is a game changing approach in our Indian Economy.